Efeito antinociceptivo do HC-030031, um antagonista seletivo do receptor de potencial transitório anquirina subtipo 1 (TRPA1), em modelos de nocicepção visceral - Pereira, Lus Mario da Silva (2012)
The description of the TRP family of receptors including TRPA1 has provided potential therapeutic targets for treating acute and chronic pain. Some studies have shown a somatic nociceptive response due to the TRPA1 receptors activation which is effectively modulated with the experimental tool, HC-030031, a TRPA1 antagonist. However, there are a few studies evaluating the role of TRPA1 receptors in visceral pain. Then aimed to investigate the role of TRPA1 in the animal models of visceral nociception induced by different substances and to explore the possible mechanisms involved. Swiss male mice (n=6) were given only Carboxymethyl cellulose (vehicle CMC 0.5%, 1 mL/kg, p.o.), the compound HC-030031 (75, 150 or 300 mg/Kg, p.o.) or L-NAME (10 or 40 mg/Kg, s.c.) alone or with L-arginine (600mg/Kg, i.p.) 1h previously a alone injection of IFO (400 mg/kg, i.p.). Visceral nociception was assessed through the von Frey test previously (T0) and 12h (T1) later IFO injection by the abdominal stimulation with a pressure meter. The results were obtained in grams (T0-T1). The bladder of these animals were also removed to weighted (BWW), analyzed and after given scores macro and microscopically. We also investigated the antinociceptive effect of HC-030031 in the model of mustard oil-induced visceral nociception. The animals were treated with CMC 0.5% or HC-030031 (18.75, 37,5 or 75 mg/kg) or Morphine (5 mg/Kg, s.c.) alone or with Naloxone (2 mg/Kg, i.p.) 1h previously the injection of Mustard oil (MO) 0,75% (MO, 50 ul/colon). Visceral nociception was assessed through the von Frey test previously (T0) and 10 min (T1) after MO injection by the abdominal stimulation with a pressure meter. The results were obtained in grams (T0-T1). In another experimental setting, the animals were treated with CMC 0.5% (1 mL/kg, p.o) or HC-030031 (18.75; 37.5 or 75mg/Kg, p.o.) previously an intraperitoneal injection with acetic acid 0.6% (AA, 10 mL/kg), zymosan (Zym, 1 mg/cavity) or misoprostol (MPT, a stable prostaglandin analogous, 1μg/cavity) and immediately had the writhing responses counted for 30 min. In order to investigate the role of resident peritoneal cells on the effect of HC-030031, we washed the peritoneal cavity of mice with heparin added PBS (30 mL) and then AA, Zym or MPT were injected i.p. A Sham group was included. Eventually, the writhing responses were recorded. Statistical analysis was performed with ANOVA/Student Newman Keul as appropriate. p<0.05 was accepted. (CEPA: Protocol 92/10). IFO induced significant (p<0.05) visceral nociception (6.25±1.08) and inflammatory response [scores to edema 2(1-3); hemorrhage 3(1-3); and bladder wet weight (42.78 ± 3.1)] in comparison with saline treated group (1.97±0.89), [0(0-0); 0(0-0); 20.01± 0.7749] respectively. Moreover, HC-030031(75) and L-NAME (10 or 40 mg/Kg) prevented in a significant manner (p<0.05) the nociceptive response (2.30±1.07; 1.58±0.860 and 2500±0.7361) respectively when compared with IFO-treated group. Although the pretreatment with L-arginine (6.844±1.235) was able to reverse the antinoceceptive effect of L-NAME 10 mg/Kg, (6.84±1.23), it failed to do the same (p>0.05) with L-NAME 40 mg/Kg (1.500±0.7361) and HC-0300031 75 mg/Kg (0.72±0.69). The same reversible effect of L-Arginine was observed for the anti-inflammatory activity of L-NAME (p<0.05). However, HC-030031 presented no anti-inflammatory effect. The antinociceptive activity of HC-030031 was also assessed in the MO nociception model. We verified that MO induced a significant (p<0.05) nociceptive behavior (6.333±0.9458) when compared to saline injected mice (1.250±0.9204). Moreover, HC-030031 prevented in a significant manner the nociceptive response elicited by MO (1.536±0.7653). Furthermore, the involvement of opioid system in the antinociceptive effect of HC-030031 as tested. We observed that morphine presented an important antinociceptive activity (0.07143±0.07143) against MO-induced nociception which was significantly reverted by naloxone pre-treatment (3.125± 1.302). On the other hand, the antinociceptive effect of HC-030031 remained in spite the injection of naloxone (2.240±1.263). In addition to that, AA, Zym and MPT induced significant writhing responses (43.71±4.43; 11.00±2.11; 9.00±2.30; respectively) which was significantly inhibited with HC-030031(18.75, 37.5 e 75 mg/kg, p.o.) treated mice in all the doses tested (29.07%, 53.35% and 41.59%, in the AA test, 55.85%, 61.03% and 71.20%, in the Zym test, 63.88%, 83.33% and 88.88%, in the MPT induced nociception, respectively to 18.75, 37.5 and 75 mg/kg doses. Eventually, the reduction of cell population in the peritoneal cavity prevented the development of writhing responses in both AA and Zym injected mice, with no effect was visualized on MPT treated mice. We the conclude that, since prostaglandin activates the nociceptor directly, it was shown that HC-030031 inhibits visceral nociception possibly through the stabilization of the neuronal ends. The antinociceptive effect of HC-030031 seems to be independent of the inhibition of inflammatory resident cells, opioid and nitric oxide pathways. This study provides perspective for the effective management of visceral pain through the modulation of TRPA1 channels.